Antiviral effects of interferon-stimulated genes in bats - Zhang, Dan; Irving, Aaron T. (Frontiers in Cellular and Infection Microbiology, 2023)
The interferon pathway is the first line of defense in viral infection in all mammals, and its induction stimulates broad expression of interferon-stimulated genes (ISGs). In mice and also humans, the antiviral function of ISGs has been extensively studied. As an important viral reservoir in nature, bats can coexist with a variety of pathogenic viruses without overt signs of disease, yet only limited data are available for the role of ISGs in bats. There are multiple species of bats and work has begun deciphering the differences and similarities between ISG function of human/mouse and different bat species. This review summarizes the current knowledge of conserved and bat-specific-ISGs and their known antiviral effector functions.